THE ANALYSIS OF CENTRAL KALIMANTAN PROVINCE APBD POSTURE FOR THE 2021-2023 PERIOD - Andi Ilmi Utami Irwan; Murniyati Yanur; Jhon Retei Alfirasandi; Ricky Zulfausan; Yunita Asmawati; Mahmuddin Sirait; Purnama Julia Utami (Universitas Pancasakti Tegal, 2023)
Decentralization empowers local governments to tailor their budgets to meet specific local development needs. However, effective planning transcends mere identification of priorities; it also involves adeptly aligning resources with long-term sustainability. This research delves into the APBD realization report of Central Kalimantan Province for the 2021-2023 period, scrutinizing how the budget is harnessed to advance community welfare in alignment with the region's vision, mission, and developmental objectives. Leveraging a combination of literature review and interviews, this study reveals that the decentralization of budgetary resources by regional governments can significantly enhance community welfare and contribute to regional development. Nevertheless, the linchpin for success lies in bolstering regional government accountability in the utilization of the APBD.